Pro ASP.NET SignalR : real-time communication in .NET with SignalR 2.1 - Nayyeri, Keyvan (Apress, 2014)
ASP.NET SignalR is the new solution to real-time communication between servers and clients in .NET. Use it to push new data to a web page or mobile device as soon as it becomes available, whether it's a notification, live chat, up-to-the-minute financial data, or a range of other exciting applications. Innovations like Google live search and live Facebook and Twitter updates are pushing users' expectations of the real-time web. With Pro ASP.NET SignalR, you can join this revolution and learn skills that will be valuable for years to come. Pro ASP.NET SignalR starts with an introduction to the real-time web. Learn about the technologies underlying the SignalR library, such as WebSockets and long-polling, and how SignalR elegantly flips between them depending on the capabilities of the client. Next, meet the concepts of hubs and persistent connections and how to use them to build the components of an ASP.NET SignalR application. Find out how to extend, test, debug, configure, scale, and host your applications, and how to target a range of clients, including Windows and iOS. The book rounds off with two case studies-a stock market price updater, and a collaborative drawing application-so you can get to grips with SignalR in a realistic scenario, using a broad range of the concepts covered in earlier chapters. As real-time updates to web and mobile apps become the norm, Pro ASP.NET SignalR will be your in-depth, one-stop companion to this new and exciting technology.